2012
DOI: 10.1152/ajpregu.00358.2012
|View full text |Cite
|
Sign up to set email alerts
|

Disassociation of insulin action and Akt/FOXO signaling in skeletal muscle of older Akt-deficient mice

Abstract: Reynolds 4th TH, Merrell E, Cinquino N, Gaugler M, Ng L. Disassociation of insulin action and Akt/FOXO signaling in skeletal muscle of older Akt-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In vivo insulin action was determined by conducting IAGT testing, a procedure that has been to detect diet-induced insulin resistance at more physiological relevant blood glucose levels than insulin tolerance testing [ 15 , 22 ]. In the fasted basal state, blood glucose values were higher in the HFD-SED mice compared to all other groups (HFD-SED: 190.1 ± 8.4 vs. HFD-WR: 142 ± 9.1 vs. LFD-SED: 122.1 ± 4.6 vs. LFD-WR: 147.9 ± 18.8).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo insulin action was determined by conducting IAGT testing, a procedure that has been to detect diet-induced insulin resistance at more physiological relevant blood glucose levels than insulin tolerance testing [ 15 , 22 ]. In the fasted basal state, blood glucose values were higher in the HFD-SED mice compared to all other groups (HFD-SED: 190.1 ± 8.4 vs. HFD-WR: 142 ± 9.1 vs. LFD-SED: 122.1 ± 4.6 vs. LFD-WR: 147.9 ± 18.8).…”
Section: Resultsmentioning
confidence: 99%
“…Excitingly, we found the interplay between Abra (STARS) and its targets, Srf and Egr1. These three TFs have an important role in the remodeling, homeostasis and metabolism of skeletal muscle [ 95 ], and appear to be under control of AKT [ 96 ]. In the SiHa Gal-7+ TAM, there is not an obvious interplay between the predicted and regulated TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, direct (Senf et al, 2010) and indirect (Senf et al, 2008) inhibition of FOXO transcription activity has been shown to attenuate disuse-induced muscle loss. The exact mechanism by which the FOXO transcription factors are activated is unclear since the FOXO transcription factors are not always activated by a decrease in Akt/PKB activity (Reynolds et al, 2012), and Akt/PKB activity is not always decreased in response to unloading (Marimuthu et al, 2011). …”
Section: Attenuation Of Disuse-induced Atrophymentioning
confidence: 99%